2012
DOI: 10.1111/j.1365-3016.2012.01292.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of n‐3 Long‐chain Polyunsaturated Fatty Acid Intake during Pregnancy on Maternal, Infant, and Child Health Outcomes: A Systematic Review

Abstract: Evidence from observational studies and randomised trials has suggested a potential association between intake of n-3 long-chain polyunsaturated fatty acids (LCPUFA) during pregnancy and certain pregnancy and birth outcomes. Marine foods (e.g. fatty sea fish, algae) and select freshwater fish contain pre-formed n-3 LCPUFA, which serve as precursors for bioactive molecules (e.g. prostaglandins) that influence a variety of biological processes. The main objective of this analysis was to summarise evidence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 76 publications
(115 reference statements)
4
96
0
4
Order By: Relevance
“…Despite this, clinical trials of n-3 PUFA supplementation demonstrate conflicting results regarding pregnancy outcome (Imhoff-Kunsch et al 2012, Larqué et al 2012. It has been suggested that this is because supplementation is often begun during mid to late gestation (w22 weeks; Larqué et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, clinical trials of n-3 PUFA supplementation demonstrate conflicting results regarding pregnancy outcome (Imhoff-Kunsch et al 2012, Larqué et al 2012. It has been suggested that this is because supplementation is often begun during mid to late gestation (w22 weeks; Larqué et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Given that n-3 PUFAs exhibit both anti-oxidative and antiinflammatory properties, maternal dietary n-3 PUFA supplementation has been proposed as a potential therapeutic intervention for placenta-related disorders. Indeed, maternal dietary supplementation with n-3 PUFAs during pregnancy can exert beneficial effects including increased gestation length and increased fetal growth (Imhoff-Kunsch et al 2012, Larqué et al 2012, Jones et al 2013a, and a reduced risk of pregnancy complications (Oken et al 2007). In this study, we review the impact of dietary n-3 PUFAs on placental function, with particular focus on placental fatty acid transport, inflammation, inflammatory resolution, oxidative status, and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Women who deliver preterm have been demonstrated to have higher levels of AA and other n-6 LCPUFA in their blood and trophoblast tissue compared to women who deliver at term (13). Furthermore, maternal dietary supplementation with marine n-3 LCPUFA has been shown in randomized controlled trials (RCT) to reduce the risk of early preterm delivery (<34 wk) (relative risk = 0.74; (95% confidence interval = 0.58, 0.94)) and result in a modest increase in birth weight (14). Due to the role of AA-derived eicosanoids in the initiation of delivery it is biologically plausible that a slight dampening of this effect by competition with n-3 LCPUFA could explain a protective effect of n-3 LCPUFA against the risk of early labor (15).…”
Section: Maternal-fetal Transfer Of Arachidonic Acidmentioning
confidence: 99%
“…A source of these long-chain fatty acids is required during pregnancy for fetal and placental development (reviewed by Mennitti et al 2015;Jones et al 2014). Maternal intake/status of n-3 LCPUFA during pregnancy and lactation has been found to positively impact maternal, infant, and child health in many systematic reviews (Yang et al 2013;Imhoff-Kunsch et al 2012;Larqué et al 2012;Horvath et al 2007). The importance of a dietary source of n-3 LCPUFA is supported by stable isotope tracer studies that found only 1%-4% of dietary ALA is converted to DHA (Pawlosky et al 2001;Emken et al 1994).…”
Section: Introductionmentioning
confidence: 99%